Is positive affect in late pregnancy protective of postpartum depression?. (16th November 2010) - Bos, S Carvalho; Macedo, A; Marques, M; Pereira, AT; Maia, B; Soares, MJ; Valente, J; Gomes, AA; Azevedo, MH
Abstract : Introduction/Aim: Postpartum depression interferes negatively with mother's well-being and infant's development. The aim of this study was to investigate whether Positive Affect in late pregnancy was a protective factor for later Postpartum depression. Methods: A total of 491 pregnant women filled in the Profile of Mood States (POMS), the Beck Depression Inventory, socio-demographic characteristics, psychosocial variables and answered a Psychiatric Interview. After delivery 272 women participated for a second time. Results: POMS factor analyses revealed a 30-item scale in pregnancy and a 27-item scale in post partum. Based on both factor analyses two dimensions of affect could be determined: a negative affect (NA) and a positive affect (PA) of affect could be determined. NA was associated with more intense depressive symptomatology, more self-perceived stress, low self-reported social support and low quality of life in pregnancy as well as post partum. By contrast, PA was negatively associated with these variables. In pregnancy, NA was a predictor of post partum depression (Diagnostic and statistical manual of mental disorders, DSM-IV/OR 2.1, 95% CI 1.3 to 3.4, p=0.003; International Classification of Diseases, ICD-10/OR 2.1, 95% CI 1.5 to 3.0, p<0.001) while PA showed a protective role (DSM-IV/OR 2.0, 95% CI 1.5 to 2.7, p=0.042). Conclusion: Opposed dimensions of affect could be appropriately assessed using POMS. Reinforcing PA in late pregnancy may help preventing Postpartum depression.